Estimation of N2 fixation by nitrogenfixing trees in the subhumid tropics using 15N dilution and difference methods - Liya, S.M.; Odu, C.T.I.; Agboola, A.A.; Mulongoy, K. (1991)
Nitrogen fixation by leguminous trees contributes nitrogen to agroforestry systems and enables farmers to grow their own nitrogen fertilizer. Estimation of the amount of nitrogen fixed is necessary to asses the value of leguminous trees. In the present paper, the difference method and the 15N isotope dilution method are used to calculate the amounts of nitrogen fixed in the first year by Leucaena leucocephala (with and without inoculation with Rhizobium), Gliricidia sepium and Albizia lebbeck.